TAFSIR FENOMENOLOGI SIMBOLIK AL-QUR’AN - Nunung Lasmana dan Ahmad Suhendra (IAIN Kediri, 2015)
the Qurâ€™anic studies in Indonesia continue to experiencing a significant growth. Lukman Abdul Qohar Sumabrata,Â Lukman Saksono, and Anharudin offered a symbolic method of interpretation. They seek to interpret the Qurâ€™anÂ with different perspectives by looking at its format and structure, leading to different interpretations of theÂ Qurâ€™an. Lukman Abdul Qahar Sumabrataâ€™s interpretation method attracted attentions from many people andÂ encouraged them to study more closely the format and structure of the Qurâ€™an. The interpretation of symbolicÂ phenomenology refers to the format and structure of the Qurâ€™an of the â€˜UthmÄni script.Keywords: al-Qurâ€™an, Fenomenologi Simbolik, Tafsir